Closed loop occlusion of the colon. total ileocolectomy with restitution of traffic - Mate, Miguel; Sarroca, Carlos; Mañana, Julio (Cirugía del Uruguay, 1974)
As a consequence of adenocarcinoma of sigmoid, a patient developed closed occlusion of colon with total necrosis o-f intestine and predominance in caecum and ascending colon. Urgency surgery consisted of total ileocolectomy with transit restitution in the same act. The patient's post-operatory evolution was good and 5 months later no recurrency was clinically evident.